Polysulfone/Silver-catecholamine (PSf/Ag-CA) mixedmatrix hybrid membrane for the removal of oil-in-water emulsions - Alizan, Anis Nazira; Senusi, Faraziehan; Amri, Nurulhuda; Zubir, Nor Aida (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
Membrane technology is recognized as a reliable and efficient method for the treatment of oily wastewater, particularly in the removal of oilin-water emulsions with droplet sizes below 20 µm. However, the fouling problem remains one of the major challenges for polymeric membranes. This study investigates the impact of incorporating silvercatecholamine nanoparticles on the performance of Polysulfone (PSf)/Silver-Catecholamine (Ag-CA) mixed-matrix hybrid membrane for oil-in-water emulsions removal. The Ag-CA nanoparticles were synthesized by mixing tannic acid and tetraethylenepentamine into a tris-HCl solution, then incorporated into the membrane dope solution. The PSf/Ag-6C1A hybrid membranes were cast using an automatic membrane casting machine via a phase inversion process, and then the permeability and separation performance of the membranes were measured using a membrane test rig to observe the flux, removal efficiency, and flux recovery ratio of the membranes. Based on the experiment, the PSf/Ag-6C1A hybrid membrane has shown increased pure water flux and high removal efficiency, as well as a flux recovery ratio compared to the pristine PSf membrane. It is shown that the silvercatecholamine nanoparticles can improve the antifouling properties of the pristine PSf membranes. The PSf/Ag-6C1A hybrid membrane exhibits enhanced surface properties with a water contact angle of 76° and an underwater oil contact angle of 130.7°. These characteristics contributed to its higher water flux (14.01 LMH), excellent removal efficiency (99.79%), and flux recovery ratio of 95.71%.